2011
DOI: 10.1053/j.gastro.2010.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Mediates Up-regulation of NF-κB, β-catenin, and Stem Cell in Response to Progastrin in Mice and HEK-293 Cells

Abstract: Background & Aims Prograstrin induces proliferation in colon crypts by activating p65NF-κ B and β-catenin. We investigated whether Annexin A2 (AnxA2), a progastrin receptor, activates NF-κB and β-catenin in vivo. Method ANXA2-null (ANXA2− /−) and wild-type (ANXA2+/+) mice were studied, along with clones of progastrin-responsive HEK-293 cells that stably expressed full-length progastrin (HEK-mGAS) or an empty-vector (HEK-C). Small interfering RNA was used to downregulate AnxA2, p65NF-κB, and β-catenin in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 48 publications
4
96
0
Order By: Relevance
“…Progastrin overexpression and its proliferative and tumor-promoting effects in colorectal cancer have been well-documented (12,42,43) and previous studies linked progastrin production with the expression of CD133, DCAMKL1, or CD44 (17)(18)(19), markers that enrich but are not specific for CSCs (20)(21)(22)(23). Importantly, these studies did not provide functional data demonstrating a role for progastrin in regulating CSCs hallmarks such as selfrenewal.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Progastrin overexpression and its proliferative and tumor-promoting effects in colorectal cancer have been well-documented (12,42,43) and previous studies linked progastrin production with the expression of CD133, DCAMKL1, or CD44 (17)(18)(19), markers that enrich but are not specific for CSCs (20)(21)(22)(23). Importantly, these studies did not provide functional data demonstrating a role for progastrin in regulating CSCs hallmarks such as selfrenewal.…”
Section: Discussionmentioning
confidence: 51%
“…We previously demonstrated that progastrin regulates the Wnt and Notch pathways in colorectal cancer (12,14), suggesting that it could affect the phenotype of colon CSCs, which rely on these pathways for their survival (15). Progastrin was shown to promote the proliferation of progenitor cells in the mouse colonic epithelium (16) and a link has been suggested between progastrin expression and populations of cells expressing CD133 (17), DCAMKL1 (18), or CD44 (19) in mouse colonic crypts and human cancer cell lines. Yet, expression of these markers is not restricted to CSCs (20)(21)(22)(23), and the functional role of progastrin on CSC self-renewal and tumor-initiating potential has not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…The Dclk1+ cells grew as organoids in nude mice, suggesting Dclk1+ cells were pluripotent, a hallmark of stem cells (18). We and others reported a significant increase in the number and intensity of Dclk1+cells in hyper proliferating mouse colonic crypts, in response to potent growth factors (19) or colon carcinogenic agents, AOM ± DSS (20), suggesting a role of Dclk1+ cells, at position 4, in hyper proliferation and carcinogenesis of colonic crypt cells. However, it soon became clear that Dclk1 is also expressed in specialized cells, called tuft cells, in the mouse colonic crypts which are enriched in Cox1/Cox2, Villin and α-Tubulin, and believed to be derived from Lgr5+ actively cycling stem/progenitor cells (21).…”
mentioning
confidence: 99%
“…PG peptide induces hyper proliferation of colonic crypts and increases colon-carcinogenesis by many fold, in response to AOM±DSS (19,20,(24)(25)(26)(27). Besides, PG is expressed by >80% of human colon cancer cell lines (hCCCs) and CRCs (28,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation